COGNITIVE MODELS AND LITERARY COMPETENCE OF JUNIOR HIGH SCHOOL STUDENTS - Bañez, Marichar M; Sarmiento, Michelle B; Bañez, Richard M (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This descriptive-correlation study examined the relationship of the public junior high school students’ perception on the relevance of cognitive models in studying literature to their literary competence. Utilizing a questionnaire and a literary competence test in gathering data, the results revealed that the 251 respondents deemed that cultural model as relevant for this model prepare them to be multi-culturally literate individuals. They also found that the vicarious experiences gained from studying literature enabled them to make personal connection with literary texts especially on the universality of human existence that afforded them to perceive personal growth model as relevant. Also, the respondents perceived language model as relevant as it provided opportunity to hone their receptive communication skills. Despite the positive perception of the respondents on the relevance of cognitive models in studying literature, the results of the administered literary competence test revealed low performance as the respondents were categorized to have Beginning to Developing levels of proficiency in literary competence along its four dimensions which was affirmed by the non-significant result when the two variables were correlated for relationship. This study calls for an intervention program to hone the literary competence of the junior high school students.